Business environment as an intervening variable of market orientation and business performance of Batik Jambi SMEs - Ade Octavia (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Batik Jambi is a unique product of Jambi Province, but the performance of batik Jambi SMEs business is still low. The purpose of the research is to analyze the role of the business environment on the relationship of market orientation, entrepreneurship orientation, and business performance. The research method used is qualitative and quantitative with interview approach, observation, documentation and sample survey. The sample of this research is Batik Jambi SMEs. Sampling used judgment sampling method. The analysis tools used are FGD and PLS (partial least square). The results show that the business environment is a variable between the relationship of market orientation and business performance, but not the intermediate variables on the relationship of entrepreneurial orientation and business performance.